Perancangan Aplikasi Jasa Kuli Bangunan Berbasis Android Menggunakan Metode Throw-Away Prototype - Marchel Thimoty Tombeng; Matthew Edgar Freeman Muju (TeIKa, 2023)
This research was conducted to design and develop an android-based application for building construction services in North Sulawesi. The main purposes which this research was conducted it is because seeing the impact of COVID-19 that effect many people lose their jobs and as the times progressed, many people were looking for work or offered jobs via the internet. This research will bring together parties who need people to work and people who need work. This concept is based on e-commerce applications that trade goods, but the difference is that these applications trade services. Service is an action that is invisible, but the results can be seen. This research will focus on the services of construction workers, carpenters, and kitchen set workers. Where a construction worker will build or renovate a building, a carpenter will make wood products (tables, cabinets, chairs), and a kitchen set service will make a kitchen set. In making this application, we will use the 'throw-away prototyping' method, where researchers will create a prototype according to user needs so that users can get an overview of the application, then implement it into an application. So, in conclusion, making this application is intended to support and make people easier to find workers and jobs related to buildings. In this study, researchers have made applications and implemented existing designs so that they can produce applications that are operational and in accordance to the needs of users.